Factors at the household and university level that influence student dropout at UNAM - Marca Maquera, Hugo; Coyla Zela, Mario; Paredes, Rene Paz (Frontiers in Education, 2025)
This study analyzes the socioeconomic, institutional, and personal factors that influence student dropout at the National University of Moquegua (UNAM), with the main objective of identifying the most significant determinants to guide effective retention strategies. Based on data collected through a face-to-face survey conducted during the first semester of 2024 with a sample of 771 students (including both regular students and dropouts), a logistic regression model was applied to estimate the marginal effects of various factors on dropout probability. Results indicate that parental motivation serves as a strong protective factor, with frequent encouragement reducing dropout risk by 7.8 percentage points and very frequent motivation by 16.8 points. In contrast, having a mother without formal education or a father working in commerce significantly increases the risk. Access to a computer and internet at home correlates with lower dropout rates. Institutionally, receiving substantial homework decreases the likelihood of dropout, while poor class scheduling (27.5 percentage points), difficulty accessing campus (20.2), and negative perceptions of library quality (10.9) raise it. Student-related factors such as being male, studying fewer hours per day, and having children are also associated with increased dropout risk. The findings underscore that university dropout is driven by a combination of structural and individual elements, highlighting the need for institutions to strengthen academic and logistical support systems while fostering supportive family environments.